Mengatasi Perilaku Off-Task pada Siswa melalui Pendekatan Konseling Behavioral SMP Negeri 5 Bukittinggi - Putri, Erlisa; Yarni, Linda (YASIN, 2023)
Verbal and non-verbal behavior is a form of off-task behavior that is raised by students, verbal here is behavior such as talking outside of learning material during the teaching and learning process, singing, screaming and so on while non-verbal is daydreaming, sleeping and other behaviors. Off-task behavior often appears and interferes with the learning process and the comfort of other students who are serious about participating in the learning process. The purpose of this study is to emphasize positive behavior, it is expected to reduce the off-task behavior that exists in students. This type of research is descriptive qualitative which in this study analyzes off-task behavior more and overcomes this behavior with behavioral counseling theory. The results of the study show that behavioristic counseling is one form of counseling that is used to modify behavior such as off-task behavior, namely negative behavior, so it is hoped that this behavioral counseling can change into positive behavior. Students as individuals are required to be able to behave well in carrying out the learning process even though there are differences between other individuals. Motivation in learning is an encouragement for students in learning activities and behavioral behavior explains that human behavior or human behavior can be changed and controlled by controlling the environmental situation that exists around humans. The learning process, both education and teaching, is a process that is aware of a goal. Education and teaching is one of the reasons behind student achievement, student behavior in situations where students study in class where there are unwanted appearances or what is called off-task.